High prevalence of Plasmodium falciparum pfcrt K76T mutation in children with sickle cell disease at a tertiary hospital in north-western Tanzania - Mongella, Stella; Enweji, Nizar; Mnong'one, Naizihjwa; Minde, Mercy; Kamugisha, Erasmus; Swedberg, Göte (Tanzania Journal of Health Research, 2014)
The high prevalence of sickle cell disease (SCD) and trait in Sub-Saharan Africa coincides with the distribution of Plasmodium falciparum malaria. Due to prolonged heavy use of chloroquine (CQ) as an antimalarial, drug resistance has developed. Many countries including Tanzania abandoned the use of CQ for uncomplicated malaria, except its use as prophylaxis in patients with sickle cell disease. This study investigated the prevalence of malaria in SCD patients and mutations associated with CQ resistance. Children diagnosed with sickle cell disease attending both outpatient clinic and those admitted at Bugando Medical Centre in north-western Tanzania were screened for malaria using thick blood smear. A dried blood spot on Whatman filter paper was also taken for polymerase chain reaction (PCR) and restriction fragment length polymorphism. Among 123 known patients with sickle cell disease, the prevalence of malaria by blood smear microscopy was 3.2% and by PCR was 13.8%. The prevalence of K76T mutation among the patients was 81.3%. The majority of the patients (72.4%) were using chloroquine prophylaxis. In conclusion, the prevalence of malaria parasitaemia among children with sickle cell disease attending BMC is low (3.2%) by microscopy but several children maintain sub patent infection detectable by PCR. The prevalence of chloroquine resistant P. falciparum in these children was higher than that previously seen in normal population in Tanzania. We recommend special attention to be paid to patients with sickle cell disease while studying the dynamics of drug resistant parasites.